The structure of denisovite, a fibrous nanocrystalline polytypic disordered `very complex' silicate, studied by a synergistic multi-disciplinary approach employing methods of electron crystallography and X-ray powder diffraction - Ira V. Rozhdestvenskaya; Enrico Mugnaioli; Marco Schowalter; Martin U. Schmidt; Michael Czank; Wulf Depmeier; Andreas Rosenauer (IUCrJ, 2017)
Denisovite is a rare mineral occurring as aggregates of fibres typically 200–500 nm diameter. It was confirmed as a new mineral in 1984, but important facts about its chemical formula, lattice parameters, symmetry and structure have remained incompletely known since then. Recently obtained results from studies using microprobe analysis, X-ray powder diffraction (XRPD), electron crystallography, modelling and Rietveld refinement will be reported. The electron crystallography methods include transmission electron microscopy (TEM), selected-area electron diffraction (SAED), high-angle annular dark-field imaging (HAADF), high-resolution transmission electron microscopy (HRTEM), precession electron diffraction (PED) and electron diffraction tomography (EDT). A structural model of denisovite was developed from HAADF images and later completed on the basis of quasi-kinematic EDT data by ab initio structure solution using direct methods and least-squares refinement. The model was confirmed by Rietveld refinement. The lattice parameters are a = 31.024 (1), b = 19.554 (1) and c = 7.1441 (5) Å, β = 95.99 (3)°, V = 4310.1 (5) Å3 and space group P12/a1. The structure consists of three topologically distinct dreier silicate chains, viz. two xonotlite-like dreier double chains, [Si6O17]10−, and a tubular loop-branched dreier triple chain, [Si12O30]12−. The silicate chains occur between three walls of edge-sharing (Ca,Na) octahedra. The chains of silicate tetrahedra and the octahedra walls extend parallel to the z axis and form a layer parallel to (100). Water molecules and K+ cations are located at the centre of the tubular silicate chain. The latter also occupy positions close to the centres of eight-membered rings in the silicate chains. The silicate chains are geometrically constrained by neighbouring octahedra walls and present an ambiguity with respect to their z position along these walls, with displacements between neighbouring layers being either Δz = c/4 or −c/4. Such behaviour is typical for polytypic sequences and leads to disorder along [100]. In fact, the diffraction pattern does not show any sharp reflections with l odd, but continuous diffuse streaks parallel to a* instead. Only reflections with l even are sharp. The diffuse scattering is caused by (100) nanolamellae separated by stacking faults and twin boundaries. The structure can be described according to the order–disorder (OD) theory as a stacking of layers parallel to (100).